The settlement patterns of the Ierapetra Isthmus (East Crete) from the Archaic to the Venetian periods, as revealed through the SettleInEastCrete Program - Coutsinas, Nadia; Katifori, Marianna; Roussos, Konstantinos; Argyriou, Athanasios (Journal of Greek Archaeology, 2022)
The project, SettleInEastCrete. Spatial Dynamics and Settlement Patterns in Eastern Crete from the Classical to the Venetian Period, sets out to determine the pattern of development of the settlements in Eastern Crete from the Classical to the Venetian period. The goal is to shed light and explain the transition from the ancient autonomous city-states to the medieval cities and villages. Special attention is given to the economic, social, political and also environmental issues that influenced that evolution. Concentrating on the eastern part of Crete was particularly effective: in the same territory and over a long chronological period, and living under very different administrative systems, we were able to trace how the population responded, moving between centralised and dispersed modes of settlement. We also looked to see if some places enjoyed longer-term occupation and the reasons for such.